PENERAPAN MEDIA PEMBELAJARAN GAME INTERAKTIF ULAR TANGGA MELALUI METODE PEMECAHAN MASALAH TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI 19 LUBUK LINGGAU - Karmala; Akmal Rijal; Nur Fitriana (Linggau Journal Science Education (LJSE), 2026)
This study was conducted to determine the mastery of learning outcomes in Pancasila Education among fifth-grade students at SDN 19 Lubuklinggau following the implementation of interactive game-based learning media combined with the problem-solving method. An experimental research method was employed, specifically a pre-experimental design featuring a single-group pre-test and post-test format. The study population consisted of all 25 fifth-grade students at SDN 19 Lubuklinggau. Data collection was carried out using a written test comprising multiple-choice questions, and data analysis was performed using the Z-test. The results yielded a calculated Z-value (Z-count) of 3.52 and a critical Z-value (Z-table) of 1.64 at a significance level of α = 5% (0.05). Since Z-count ≥ Z-table (3.52 ≥ 1.64), the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted; this indicates that the use of the "Snakes and Ladders" interactive game integrated with the problem-solving method resulted in significant learning mastery for the fifth-grade students at SDN 19 Lubuklinggau in the subject of Pancasila Education.